Pelatihan Kepemimpinan dan Peranan Pokdarwis Dalam Pengembangan Wisata Pulau Putri di Kabupaten Karawang - Eki Aditiya Nugraha; Denisya Kharisma Jelita Puteri; Tatiek Yuniarti; Saepudin Saepudin (IKRA-ITH ABDIMAS, 2023)
The Tourism Awareness Group (POKDARWIS) needs to be formed in SegarjayaVillage, Batujaya District, Karawang Regency, West Java with the aim of optimizing thepotential of the village. In Pokdarwis, leadership is needed that can move all members, so thatall people realize the magnitude of the tourism potential which in the future can increaseresidents' income. This group can be a forum for residents to develop their area as a touristvillage. can be an implementation method to foster a leadership spirit and move Pokdarwiscarried out by gathering community leaders and especially young people to be givenunderstanding and to be able to create creative things in their villages which have the naturalpotential of Pulau Putri beach, ancient temples, and typical processed products. JembretTerasi. Another thing to do is work with the Tourism Community in Karawang Regency tointroduce and help promote tourism in Segarjaya Village. The result of the activities carriedout was the growing awareness of the importance of empowering tourism potential inSegarjaya Village. In addition, the tourism community presented can introduce tourism inKarawang more broadly through its media. As a result, tourists on the Putri Island beach haveincreased. Putri Island Tourism Beach and Educational Tourism (Making Jembret Terasi)which can be packaged into attractive tour packages in the future. Tourism is stretched, thepeople's standard of living increases.